SOSIALISASI STOP BULLYING (PERUNDUNGAN) DI SMA/SMK MUHAMMADIYAH SINGKUT KECAMATAN SINGKUT KABUPATEN SAROLANGUN - Rohayati, Wahyu (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2021)
The younger generation is the foundation and capital of national development. Therefore, parents, educators, and the government are expected to be serious about providing them with the best education. Understanding and actions to protect children's rights are guaranteed in the 1945 Constitution of the Republic of Indonesia, Article 28B paragraph (2), which states that every child has the right to survival, growth, and development, as well as the right to protection from violence and discrimination. However, in practice, various forms of violence against children still occur, including bullying. The growing needs of society worldwide have made information technology play a crucial role, both in the present and the future. The role of technology also influences students in schools, as technology can enable students to engage in bullying behavior toward their peers. Consequently, it cannot be denied that bullying incidents are on the rise among students, largely due to the lack of awareness among the public and students regarding such behavior.On that basis, it is necessary to raise awareness about stopping bullying among students at SMK/SMA Muhammadiyah Singkut. This awareness campaign is carried out through 1). Delivering the material directly/lecture on the definition, impacts, and regulations related to bullying, 2). Sharing, discussing, asking questions, and engaging in dialogue, giving students the opportunity to participate in this awareness campaign, 3). Using audio-visual aids, electronic audio-visual equipment will be used to display photos/illustrations of bullying victims, present materials, etc. The outcomes of this outreach program include increased knowledge among students about stopping bullying, enhanced understanding of legal regulations related to bullying, and awareness of the impacts on bullying victims.